Brain-wide mapping and region-specific cellular characterization of Trhr1 reporter-labeled cells in mice using VISoR imaging - Mingrui Zhang; Su Ma; Hanbo Guo; Yuehan Ji; Hong Ni; Rongjing Ge; Yuanyuan Wang; Yong Jiang; Lianjun Li; Yuyang Zhu; Qian Wang; Lingxiao Guo; et al. (Brain Structure and Function, 2026)

Sex differences in resting-state hypothalamic connectivity and its relationship with negative emotion and behavior measures in young adults - Guangfei Li; Yiran Shao; Lin Yang; Yanan Su; Mengmeng Wang; Zhao Zhang; Xiaoyi Sun; Bao Li; Xiaolin Wang; Yu Chen; Guangyu Bin; Chiang-Shan R. Li (Brain Structure and Function, 2026)

Cross-modality comparison between structural and metabolic networks in individual brain based on the Jensen-Shannon divergence method: a healthy Chinese population study - Yu-Lin Li; Mou-Xiong Zheng; Xu-Yun Hua; Xin Gao; Jia-Jia Wu; Chun-Lei Shan; Jun-Peng Zhang; Dong Wei; Jian-Guang Xu (Brain Structure and Function, 2023)

A comparative study of the superior longitudinal fasciculus subdivisions between neonates and young adults - Wenjia Liang; Qiaowen Yu; Wenjun Wang; Thijs Dhollander; Emmanuel Suluba; Zhuoran Li; Feifei Xu; Yang Hu; Yuchun Tang; Shuwei Liu (Brain Structure and Function, 2022)
The superior longitudinal fasciculus (SLF) is a complex associative tract comprising three distinct subdivisions in the frontoparietal cortex, each of which has its own anatomical connectivity and functional roles. However, many studies on white matter development, hampered by limitations of data quality and tractography methods, treated the SLF as a single entity. The exact anatomical trajectory and developmental status of each sub-bundle of the human SLF in neonates remain poorly understood. Here, we compared the morphological and microstructural characteristics of each branch of the SLF at two ages using diffusion MRI data from 40 healthy neonates and 40 adults. A multi-shell multi-tissue constrained spherical deconvolution (MSMT-CSD) algorithm was used to ensure the successful separation of the three SLF branches (SLF I, SLF II and SLF III). Then, between-group differences in the diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI) metrics were investigated in all the SLF branches. Meanwhile, Mahalanobis distances based on all the diffusion metrics were computed to quantify the maturation of neonatal SLF branches, considering the adult brain as the reference. The SLF branches, excluding SLF II, had similar fibre morphology and connectivity between the neonatal and adult groups. The Mahalanobis distance values further supported the notion of heterogeneous maturation among SLF branches. The greatest Mahalanobis distance was observed in SLF II, possibly indicating that it was the least mature. Our findings provide a new anatomical basis for the early diagnosis and treatment of diseases caused by abnormal neonatal SLF development.

Mapping fetal brain development based on automated segmentation and 4D brain atlasing - Haotian Li; Guohui Yan; Wanrong Luo; Tingting Liu; Yan Wang; Ruibin Liu; Weihao Zheng; Yi Zhang; Kui Li; Li Zhao; Catherine Limperopoulos; Yu Zou; et al. (Brain Structure and Function, 2021)

Dissociable plasticity of visual-motor system in functional specialization and flexibility in expert table tennis players - Dazhi Yin; Xuefei Wang; Xiaoyou Zhang; Qiurong Yu; Yu Wei; Qing Cai; Mingxia Fan; Lin Li (Brain Structure and Function, 2021)

Delineating the organization of projection neuron subsets in primary visual cortex with multiple fluorescent rabies virus tracing - Liang Li; Yajie Tang; Leqiang Sun; Jinsong Yu; Siheng Zhang; Hui Gong; Hannah C. Webber; Xiaoyu Zhang; Zhe Hu; Xiangning Li; Khaista Rahman; Xiangwei Shi; et al. (Brain Structure and Function, 2021)

Structural and functional brain signatures of endurance runners - Long Cao; Yuanchao Zhang; Ruiwang Huang; Lunxiong Li; Fengguang Xia; Liye Zou; Qian Yu; Jingyuan Lin; Fabian Herold; Stephane Perrey; Patrick Mueller; Milos Dordevic; et al. (Brain Structure and Function, 2021)

The association between prenatal endocrine-disrupting chemical exposure and altered resting-state brain fMRI in teenagers - Jun-Cheng Weng; Chi Ieong Hong; Jeng-Dau Tasi; Chao-Yu Shen; Pen-Hua Su; Shu-Li Wang (Brain Structure and Function, 2020)

Impact of COMT haplotypes on functional connectivity density and its association with the gene expression of dopamine receptors - Jie Tang; Yanjun Li; Jiayuan Xu; Wen Qin; Qian Su; Qiang Xu; Bing Liu; Tianzi Jiang; Chunshui Yu (Brain Structure and Function, 2019)

Genetic labeling reveals temporal and spatial expression pattern of D2 dopamine receptor in rat forebrain - Qing Yu; Ying-Zi Liu; Yan-Bing Zhu; Yao-Yi Wang; Qian Li; Dong-Min Yin (Brain Structure and Function, 2019)

A domain-general brain network underlying emotional and cognitive interference processing: evidence from coordinate-based and functional connectivity meta-analyses - Taolin Chen; Benjamin Becker; Julia Camilleri; Li Wang; Shuqi Yu; Simon B. Eickhoff; Chunliang Feng (Brain Structure and Function, 2018)

Uhrf2 deletion impairs the formation of hippocampus-dependent memory by changing the structure of the dentate gyrus - Xiao-Rong Chen; Shi-Cheng Sun; Shuai-Wen Teng; Liang Li; Yi-Fan Bie; Hui Yu; Da-Li Li; Zhe-Yu Chen; Yue Wang (Brain Structure and Function, 2018)

Commonly preserved and species-specific gyral folding patterns across primate brains - Xiao Li; Hanbo Chen; Tuo Zhang; Xiang Yu; Xi Jiang; Kaiming Li; Longchuan Li; Mir Jalil Razavi; Xianqiao Wang; Xintao Hu; Junwei Han; Lei Guo; et al. (Brain Structure and Function, 2017)

Neuropeptide S ameliorates olfactory spatial memory impairment induced by scopolamine and MK801 through activation of cognate receptor-expressing neurons in the subiculum complex - Yu-Feng Shao; Can Wang; Jun-Fan Xie; Xiang-Pan Kong; Le Xin; Chao-Yu Dong; Jing Li; Wen-Ting Ren; Yi-Ping Hou (Brain Structure and Function, 2016)

Myosin II regulates actin rearrangement-related structural synaptic plasticity during conditioned taste aversion memory extinction - Ai-Ling Bi; Yue Wang; Shuang Zhang; Bo-Qin Li; Zong-Peng Sun; Hong-Sheng Bi; Zhe-Yu Chen (Brain Structure and Function, 2015)

DISC1 Ser704Cys impacts thalamic-prefrontal connectivity - Bing Liu; Lingzhong Fan; Yue Cui; Xiaolong Zhang; Bing Hou; Yonghui Li; Wen Qin; Dawei Wang; Chunshui Yu; Tianzi Jiang (Brain Structure and Function, 2015)

Differential expression of VGLUT1 or VGLUT2 in the trigeminothalamic or trigeminocerebellar projection neurons in the rat - Shun-Nan Ge; Zhi-Hong Li; Jun Tang; Yunfei Ma; Hiroyuki Hioki; Ting Zhang; Ya-Cheng Lu; Fu-Xing Zhang; Noboru Mizuno; Takeshi Kaneko; Ying-Ying Liu; Mandy Siu Yu Lung; et al. (Brain Structure and Function, 2014)

Significantly differential diffusion of neuropathological aggregates in the brain of transgenic mice carrying N-terminal mutant huntingtin fused with green fluorescent protein - Pei-Hsun Cheng; Chia-Ling Li; Lu-Shiun Her; Yu-Fan Chang; Anthony W. S. Chan; Chuan-Mu Chen; Shang-Hsun Yang (Brain Structure and Function, 2013)

Differential neuronal changes in medial prefrontal cortex, basolateral amygdala and nucleus accumbens after postweaning social isolation - Yu-Chun Wang; Ue-Cheung Ho; Meng-Ching Ko; Chun-Chieh Liao; Li-Jen Lee (Brain Structure and Function, 2012)